Characterization of Nuclear Targets and Thin Films Using Ion-Beam Techniques - Kanellakopoulos, A.; Lagaki, V.; Mertzimekis, T. J.; Paneta, V. (HNPS Advances in Nuclear Physics, 2012)
We report on the characterization of nuclear targets and thin films using standard ion-beam techniques at the Tandem Accelerator Laboratory (TAL) of INPP, NCSR “Demokritos”. The characterization was carried out with the application of Rutherford Backscattering and standard Nuclear Reaction Anal- ysis using both large and small goniometric chambers available at TAL. Results from the measurements and simulations are presented.